(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Litkovets E. Studies of interdisciplinary relationships in the formation of graphic skills to primary school students. The article is sanctified to research of intersubject connections in forming of graphic abilities for the students of initial classes.